Perceived costs and benefits of ifrs adoption in Italian medium size entities - Carini, Cristian; Teodori, Claudio; Veneziani, Monica; Dunne, Theresa; Helliar, Christine (Piccola Impresa / Small Business, 2011)
Since 2005, Italy is one country where SMEs (under certain conditions) have been given the option to adopt full IFRS if they so wish. A feature of Italy is that it is a country which is very dependent upon its SME sector for a vibrant and healthy economy. In this context, it is interesting to see initially how many Italian companies, in particular medium-sized, opted voluntarily for the full IFRS compared to those that still apply the Italian GAAP, and subsequently focus attention on the reasons for the choice. More specifically, having ascertained the high number of companies that do not apply the IFRS, the aim of the study was to investigate the reasons for the non-adoption decision, via the use of a questionnaire which concentrates on analysis of the costs and benefits perceived. In view of the same conceptual framework used by the IASB in dictating the standards both for the listed companies and for the SMEs, this study could be useful for SMEs who are required to prepare accounts using IFRS issued in July 2009 for accounting periods ending on or after 31 December 2012, in order to overcome in time the possible obstacles and prepare best for the transition to the new standards.